Facing the Landscape of Cries: An Aesthetics of Resistance - Prinz, Julia D. E. (The Merton annual, 2025)
The biblical understanding of "aesthetics" [aesthesis] as deep understanding and discernment - along with the unique interplay in Thomas Merton's life between mysticism, aesthetics and political resistance - undergirds three dimensions of an "aesthetics of resistance" sketched in this essay. (1) We place Merton in conversation with Wassily Kandinsky and the early twentieth-century "Blue Rider" art movement to evoke "the aesthetics of truth-telling" constitutive of genuine prophets. (2) The striking resonances between Merton and two other artists - Paul Klee and Käthe Kollwitz - suggest the possibility of an "aesthetics of lamentation" woven through the witness of the martyr. (3) In the mystical intimations limned in Merton's "Rain and the Rhinoceros," an "aesthetics of healing" allows even the most damaged of human beings or human situations to find "the gate of heaven" in all that surrounds us.